Assessing crisis management competencies: a case study of Pasir Gudang City Council - Muhammad, Norlina; Arshad, Mohd Mursyid; Ismail, Ismi Arif; Md Rami, Ahmad Aizuddin (Macrothink Institute, 2021)
In this modern era of globalisation, the role of leaders and employees in handling crises and problems is very important. This study aims to gather as much understanding as possible through different perspectives. This study was conducted using qualitative methods involving eight informants in a number of in-depth interviews until data saturation has been reached. During the interview sessions, questions were asked based on the preparation of an interview protocol. Data analysis discovered four main themes related to crisis management competencies, namely “excellent work culture”, “dynamic thinking competency learning”, “efficient organisational production”, and “responsive governance development”. Overall, the data acquisition indicates that crisis management competencies give further understanding to employees on how to deal and handle upcoming crisis and to prepare it from happening in the future. At the same time, the management and employees need to implement organisational learning as a process to formulate strategies and improve the service quality to external parties such as customers and stakeholders.